HUBUNGAN PENGETAHUAN DAN SIKAP IBU HAMIL TENTANG ANTENATAL CARE (ANC) DENGAN KEJADIAN IBU HAMIL RESIKO TINGGI DI PUSKESMAS RAWASARI KOTA JAMBI - Hes ty (Menara Ilmu, 2018)
An increased risk of high-risk pregnancy means that more and more pregnant womenare at risk of getting a bad pregnancy outcome. This condition is exemplified that the use ofalcohol during pregnancy is associated with miscarriage (spontaneous abortion), mentalretardation, low birth weight (LBW) and fetal alcohol syndrome. Sexually transmitteddiseases (STDs) during pregnancy of an increasing incidence of AIDS are also linked toneonatal defects and diseases.This research uses quantitative research with cross sectional research design that is astudy to study correlation between independent variable and dependent variable byapproach, observation or data collection at one time. Based on the result of research ofpregnant mother with knowledge of less good amounted to 44 respondents (86,3%) there washigh risk pregnancy incidence, and mother with bad knowledge but did not experience highrisk pregnancy incidence amounted to 7 respondents (13,7%). While mothers with goodknowledge have experienced high risk pregnancy incidence amounted to 13 respondents(13.5%) and well-informed mothers did not experience high risk pregnancy incidenceamounted to 27 respondents (67.5%). Based on the result of research of pregnant motherwith bad attitude amounted to 53 respondents (70,7%) there was high risk pregnancyincidence, and mother with bad attitude but did not experience high risk pregnancy incidenceamounted to 22 respondents (29,3%). It is hoped that this research can further improveantenatal care service and motivate mothers to come to health center or health service toconduct routine pregnancy check, more cooperative to health service and become referenceto see the activeness level of pregnant mother in doing ante natal care visit to Puskesmas orappropriate health services.Keywords: Antenatal care, Knowledge, Attitude